PERGULATAN PENDIDIKAN AGAMA ISLAM DI KAWASAN MINORITAS MUSLIM - Abdul Wahib (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2011)
This study was conducted with a qualitative approach. Data obtained by in-depth interviews, observation and documentation. Data were analyzed by phenomenological qualitative analysis model. This study concluded: (1) about the life of the Muslim minority in the school before and after the bombing; With imitate the concept of immersion, the good relations established between the Hindu-Muslim, but the bombs are up to two times it has damaged the relationship patterns that have progress, (2) the internal problems of PAI Teachers: The teachers of Islamic religious education in Bali faced a different problem that encompasses many domains of life. In school /classroom, in social life and so on, (3) materials additional Islamic Education, also called local curriculum include: Instilling a sense of respect for people who embrace different beliefs.